Integrating MALL in Video Projects: An Innovative Approach in Methods of Language Teaching - Marisa Lina; Juwita Artanti Kusumaningtyas (Universitas Majalengka, 2026)
The integration of technology in language education has become a necessity, yet pre-service teachers often struggle to bridge pedagogical theories with practical digital implementation. This research addresses the challenge of enhancing pedagogical skills through a mobile-assisted approach in the Methods of Language Teaching (MLT) course. The primary objective of this study was to investigate the implementation of Mobile-Assisted Language Learning (MALL) within a collaborative video project. This qualitative study involved 35 pre-service teachers at a state university in Central Java, Indonesia. Data were collected through participant observations of the video production process, analysis of the final digital artifacts, and open-ended questionnaires. The research results indicated that the use of MALL in video projects significantly enhanced students' digital pedagogical content knowledge and engagement. Students successfully transformed theoretical language teaching methods into engaging visual content using mobile applications. Furthermore, the findings revealed a marked reduction in speaking anxiety and an increase in creative collaboration. This study concludes that project-based MALL provides a flexible and effective framework for preparing future educators to navigate the digital demands of modern ELT classrooms.